Comparing the Concept of Scarcity: Conventional vs. Islamic Economics - Bhinekawati, Risa (Journal of Applied Business and Economics, 2021)
Scarcity is a central issue in economics as a social science. While conventional economics recognize both absolute and relative scarcities, Islamic economics recognize only relative scarcity and there is no absolute scarcity, because Allah provides sufficient resources for the whole world. The real problem of economy according to Islamic economics is the moral value or human behavior in managing relative scarcity to achieve welfare and justice. Human behavior can be governed when an individual is aware of his roles as a protector of earth and a servant of God in pursuing spiritual and material goals.